Low-cost ultrasensitive flexible carbon fiber-based biosensor for the detection of SARS-CoV-2 in human saliva - Steffane Q. Nascimento; Rodrigo M. Iost; Thiago C. Oliveira; Rafael N. Colombo; Luana C.I. Faria; Thiago Bertaglia; Jéssica C. Pacheco; Mona N. Oliveira; Erika R. Manuli; Geovana M. Pereira; Ester C. Sabino; Frank N. Crespilho (Biosensors and Bioelectronics: X, 2024)
The ongoing COVID-19 pandemic continues to have a significant impact on our daily lives, necessitating the rapid development of early diagnostic tools to mitigate the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreaks. In this context, biosensor technology has emerged as a highly promising strategy to address the challenges of low sensitivity, specificity, and high cost associated with clinical diagnosis. In this study, we present a novel and cost-effective approach for the rapid detection of SARS-CoV-2 using miniaturized flexible carbon fiber (FCF) electrodes that are modified with immunoglobulin G (IgG). Our strategy take advantage of on the antigen-antibody interaction (IgG-SARS-CoV-2) and leverages the surface chemistry characteristics of FCF to achieve signal amplification. Under standard conditions, we achieved a remarkable detection limit of 0.16 pg mmL−1 for the SARS-CoV-2 RBD protein. Additionally, when analyzing human saliva samples, our biosensing approach demonstrated good agreement with RT-PCR results, specifically for patients who tested positive for SARS-CoV-2. The sensitivity, selectivity, and accuracy of our approach were approximately 93.3%.